Cloning and Characterization of a Novel Chondroitin Sulfate/Dermatan Sulfate 4-O-Endosulfatase from a Marine Bacterium - Wang, Wenshuang (J Biol Chem, 2015)
Sulfatases are potentially useful tools for structure-function studies of glycosaminoglycans (GAGs). To date, various GAG exosulfatases have been identified in eukaryotes and prokaryotes. However, endosulfatases that act on GAGs have rarely been reported. Recently, a novel HA and CS lyase (HCLase) was identified for the first time from a marine bacterium (Han, W., Wang, W., Zhao, M., Sugahara, K., and Li, F. (2014) J. Biol. Chem. 289, 27886–27898). In this study, a putative sulfatase gene, closely linked to the hclase gene in the genome, was recombinantly expressed and characterized in detail. The recombinant protein showed a specific N-acetylgalactosamine-4-O-sulfatase activity that removes 4-O-sulfate from both disaccharides and polysaccharides of chondroitin sulfate (CS)/dermatan sulfate (DS), suggesting that this sulfatase represents a novel endosulfatase. The novel endosulfatase exhibited maximal reaction rate in a phosphate buffer (pH 8.0) at 30 °C and effectively removed 17–65% of 4-O-sulfates from various CS and DS and thus significantly inhibited the interactions of CS and DS with a positively supercharged fluorescent protein. Moreover, this endosulfatase significantly promoted the digestion of CS by HCLase, suggesting that it enhances the digestion of CS/DS by the bacterium. Therefore, this endosulfatase is a potential tool for use in CS/DS-related studies and applications.